Plasma lactate as a predictor of early childhood neurodevelopmental outcome of neonates with severe hypoxaemia requiring extracorporeal membrane oxygenation. Issue 1 (January 1996) - Cheung, P. Y.; Robertson, C. M.; Finer, N. N.
Abstract : Although plasma lactate concentration has been widely used as an indicator of tissue hypoxia, no clinical study has been conducted to relate these values to the neurological outcome of sick neonates. Seventeen consecutively cared for and surviving neonates with severe hypoxaemia requiring extracorporeal membrane oxygenation (ECMO) were evaluated at a mean age of 19.6 months. The serial plasma lactate concentrations were significantly correlated with the scores of the Bayley Scales of Infant Development. Admission and peak plasma lactate of < or = 15 mmol/l predicted favourable outcome (MDI and PDI > 70 and no disability): sensitivity 100%, specificity 88%, positive predictive value 90%, and negative predictive value 100%. Plasma lactate values could help predict neurodevelopmental outcome in these sick neonates.